Meta-Analysis the Effects of Loneliness on Depression in Elderly - Muhammad Zainul Arifin; Hasdianah Hasan Rohan (Indonesian Journal of Global Health Research, 2023)
The impact loneliness on health and well-being is recognized globally as a public health problem. Loneliness can be experienced at any age, especially in the elderly. This study aimed to analyze and estimate the influence of loneliness on depression in the elderly. This type of research is meta-analysis and was carried out according to the PRISMA flow chart and the PICO model. P: elderly, I: loneliness, C: not lonely, O: depression. Search for articles in this study through databases that include PubMed, ProQuest, and Springer Link with keywords "Loneliness"[Mesh] OR “Lonely” [tiab] OR "social isolation' [tiab] AND "Depression"[tw] OR “stress” AND “Elderly” OR "older people" [tiab] AND "Multivariate analysis" [Mesh] [tiab]. The data were analyzed using the Review Manager software (RevMan 5.3). The result showed that elderly people who experience loneliness will increase the incidence of depression by 1.65 times compared to elderly people who are not lonely, this showed that loneliness is a risk factor for depression in the elderly, and its statistically significant (aOR= 1.65; 95% CI= 1.13 to 2.42; p= 0.010).